Penyuluhan Tentang Pijat Bayi di Gampong Barat Kecamatan Nisam Kabupaten Aceh Utara - Erlina, Erlina; Nurul Huda; Marduati, Marduati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Infancy is a crucial golden period for determining the quality of a child's future growth and development. Infant massage has long been recognized for its numerous benefits for infant growth and development. Various studies have shown that infant massage can increase weight gain, improve sleep quality, strengthen the immune system, and aid digestion. Many parents still lack understanding of infant massage. Some assume that infant massage is only performed on sick babies and is performed by traditional healers or medical personnel skilled in infant massage. The purpose of this community service is to increase mothers' knowledge about infant massage through outreach. The target audience was 22 mothers with babies in Gampong Barat, Nisam District, North Aceh Regency. The implementation method used was lectures, discussions, and demonstrations. The results showed that the majority of mothers' knowledge was in the good category after the outreach. This was due to the mothers' enthusiasm in participating in the outreach. Outreach is an effective method for increasing knowledge. Mothers are expected to continue to improve their knowledge about infant massage by increasing their interest in seeking information, whether through reading books, the media, or other sources.